Hemicellulosic bioethanol production from fast-growing Paulownia biomass - Domínguez, E. (2021)
In order to exploit a fast-growing Paulownia hardwood as an energy crop, a xylose-enriched hydrolysate was obtained in this work to increase the ethanol concentration using the hemicellulosic fraction, besides the already widely studied cellulosic fraction. For that, Paulownia elongata x fortunei was submitted to autohydrolysis treatment (210 °C or S0 of 4.08) for the xylan solubilization, mainly as xylooligosaccharides. Afterwards, sequential stages of acid hydrolysis, concentration, and detoxification were evaluated to obtain fermentable sugars. Thus, detoxified and non-detoxified hydrolysates (diluted or not) were fermented for ethanol production using a natural xylose-consuming yeast, Scheffersomyces stipitis CECT 1922, and an industrial Saccharomyces cerevisiae MEC1133 strain, metabolic engineered strain with the xylose reductase/xylitol dehydrogenase pathway. Results from fermentation assays showed that the engineered S. cerevisiae strain produced up to 14.2 g/L of ethanol (corresponding to 0.33 g/g of ethanol yield) using the non-detoxified hydrolysate. Nevertheless, the yeast S. stipitis reached similar values of ethanol, but only in the detoxified hydrolysate. Hence, the fermentation data prove the suitability and robustness of the engineered strain to ferment non-detoxified liquor, and the appropriateness of detoxification of liquor for the use of less robust yeast. In addition, the success of hemicellulose-to-ethanol production obtained in this work shows the Paulownia biomass as a suitable renewable source for ethanol production following a suitable fractionation process within a biorefinery approach.